Catherine Breillat - Keesey, Douglas (French film directors., 2016)
This is the first English-language book on controversial female director Catherine Breillat, whose films include Romance, A ma soeur! (Fat Girl), Anatomy of Hell and The Last Mistress. This volume explores the director's complex relation to religion and to feminism, and it examines the differences between Breillat's films and patriarchal pornography, engaging in detailed analysis of her intimate scenes between men and women. Keesey also discusses the literature, films, paintings and photos that have influenced Breillat's work, and extends this to show how Breillat's films have influenced other.